ANALISIS PENERAPAN STANDAR AKUNTANSI PEMERINTAHAN BERBASIS AKRUAL - Ailen Safitri; Meyzi Heriyanto; Mariaty Ibrahim (Universitas Riau, 2017)
Analysis of Implementation of Accrual Based Government Accounting Standards. This study aims to analyze the readiness in the application of accounting standards based on government accruals in the District Government of Meranti Islands. The research type is quantitative, with population of unit apparatus in government of Meranti Islands Regency. Data collection techniques are questionnaires and interviews. Samples were taken as many as 80 people with purposive sampling method. Informant Research 5 people. The analytical method used is quantitative descriptive. Based on data analysis using Human Resource Indicators, Commitment, Information System and Standard Operating Procedure, it can be concluded that the Regional Government of Meranti Islands Regency is ready to implement the implementation of Government Regulation No. 71 of 2010 on accounting standard of government based on full accrual, but still lack of human resources Which background accounting, especially in the financial section which is also one of the indicators in the readiness of the implementation of PP No. 71 of 2010. Lack of bimtek and training on PP No. 71 Year 2010 is one of the existing human resource constraints are not too understand about the accrual-based accounting is .